Characteristic of flexural cracks in reinforced concrete beam under low cycle dynamic load / Md Rasul Mohamad Nor and Siti Hawa Hamzah - Mohamad Nor, Md Rasul; Hamzah, Siti Hawa (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2006)
Reinforced concrete has been widely used in Malaysian construction industry. Both residential and industrial buildings have been constructed using reinforced concrete and at present, many more high-rise structures are constructing with it. Dynamic load on reinforced concrete structure has been widely studied especially on bridges. However, with the recent seismic activity surrounding Malaysia's continent, it has been an interest to determine the dynamic response of reinforced concrete structure in building. This investigation focused on reinforced concrete beam of grade 30 with water cement ratio 0.3, tested under dynamic load influence. A total of 9 beams of size 125mm x 150mm x 1400mm were cast and tested. Deflections and crack patterns during serviceability and ultimate limits were investigated. The investigation shows that the beam deflected between 0.608 mm to 2.527 mm when subjected to 1 million and 3 million cycles during serviceability and ultimate limits. Flexural crack initiated at mid span both under static and dynamic load influence.